2014
DOI: 10.1016/j.catcom.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide catalyzed reduction of acid chlorides to aldehydes with hydrosilanes

Abstract: Iron-catalyzed reduction of acid chlorides to the corresponding aldehydes with a hydrosilane as a reducing agent has been developed. A simple mixture of a commercially available iron oxide (FeO) and tris(2,4,6-trimethoxyphenyl)phosphine (TMPP) as a catalyst realized the reduction of acid chlorides to the corresponding aldehydes under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Tsuji et al reported that an iron catalyst, generated in situ from iron oxide (FeO) in the presence of phenyl silane as reducing agent and tris(2,4,6-trimethoxyphenyl)phosphine, was able to reduce at room temperature various aliphatic acyl chlorides into the corresponding aldehydes in moderate yields (36-58%) [32]. No other triaryl phosphine, or trialkyl phosphine improved the catalytic activity.…”
Section: Scheme 23mentioning
confidence: 98%
“…Tsuji et al reported that an iron catalyst, generated in situ from iron oxide (FeO) in the presence of phenyl silane as reducing agent and tris(2,4,6-trimethoxyphenyl)phosphine, was able to reduce at room temperature various aliphatic acyl chlorides into the corresponding aldehydes in moderate yields (36-58%) [32]. No other triaryl phosphine, or trialkyl phosphine improved the catalytic activity.…”
Section: Scheme 23mentioning
confidence: 98%
“…In 2014, Tsuji and co-workers described a procedure for a Rosenmund-like reduction of carboxylic acid chlorides with phenylsilane to provide aldehydes in moderate yields . The transformation was performed in toluene at 60–120 °C using iron(II) oxide in combination with tris(2,4,6-trimethylphenyl)phosphine (TMPP) as catalytic system.…”
Section: Reductionsmentioning
confidence: 99%
“…Noticeably, aldehydes were obtained starting from more reactive acyl chlorides using a catalytic system generated from FeO (20 mol %) and tris­(2,4,6-trimethoxyphenyl)­phosphine (TMPP, 5.0 mol %) in the presence of PhSiH 3 (1.12 equiv) in toluene at 60–120 °C for 20 h …”
Section: Hydrosilylationmentioning
confidence: 99%
“…A final reductive elimination produced the silylated acetal and regenerated the unsaturated iron(0) active species. 369 Noticeably, aldehydes were obtained starting from more reactive acyl chlorides using a catalytic system generated from FeO (20 mol %) and tris(2,4,6-trimethoxyphenyl)phosphine (TMPP, 5.0 mol %) in the presence of PhSiH 3 (1.12 equiv) in toluene at 60−120 °C for 20 h. 371 3.4.4. Carboxylic Acids.…”
Section: Aldehydes and Ketonesmentioning
confidence: 99%